Pengembangan Media Aurbook (Augmented Reality Book) untuk Meningkatkan Hasil Belajar Siswa Kelas IV Pada Pembelajaran IPAS Materi Kearifan Lokal - Vina Indriana Rukmana; Novi Setyasto (Postgraduate, University of Mataram, 2025)
The purpose of this study was to develop and test the feasibility, effectiveness, and practicality of the Aurbook (Augmented Reality Book) media in order to improve student learning outcomes. This research is categorized as development research (R&D) using the Borg and Gall model. A total of 36 fourth-grade students of SDN Kalinegoro 3 in the 2024/2025 academic year were involved in this study, with a small-scale trial conducted on 12 class IVA students and a large-scale trial on 24 class IVB students. The validation results from media, material, and language experts show that the Aurbook media is declared